ANALISIS YURIDIS PELUANG PARTISIPASI DESA ADAT DALAM PEMBENTUKAN HUKUM (Lex Journal: Kajian Hukum & Keadilan, 2018)
The Participation formation of the law to be understood as law formation that involving the community in every stage process. Within formation of the law to involve formal actor and non formal actor. Formal actors are executive, legislative and judicative. Non formal actors are the communities and desa adat. In this research will be explained arrangement of the desa adat participation opportunity and the stage of desa adat participation. The research uses normative legal methods with statue approach and legal hermeneutic approach. The results of the research show that there is a clear arrangement about opportunities participation of desa adat in law formation. Arrangement opportunities participation in legal instruments have fulfilled the purpose of law and also philosophy, sociology and juridical. The forming of desa adat opportunities participation within law formation be at stage of ante legislative, legislative and post legislative.Keywords : Opportunity, Participation, Desa Adat, Formation of law.